Discontinuation of long acting reversible contraceptive use and its determinants among women in Ethiopia: Systematic review and meta-analysis - Gebeyehu, Natnael Atnafu; Tegegne, Kirubel Dagnaw; Biset, Gebyaw; Sewuyew, Dagne Addisu; Alemu, Biresaw Wassihun; Yitayew, Alemker Mola (Frontiers in Public Health, 2022)
Introduction Contraception discontinuation is a major public health issue that leads to unwanted pregnancies and unsafe abortions. Therefore, this systematic review and meta-analysis aimed to estimate discontinuation of contraceptives and its determinants in Ethiopia. Methods PubMed, Google Scholar, Scopus, Science Direct, and Addis Ababa University online library were searched. Data were extracted using Microsoft Excel and analyzed using STATA statistical software (v. 14). Publication bias was checked by forest plot, Begg's rank test, and Egger's regression test. To look for heterogeneity, I2 was computed, and an overall estimated analysis was carried out. Subgroup analysis was done by region, study setting, and publication. The pooled odds ratio for associated factors was also computed. Results Out of 654 studies assessed, 20 met our criteria and were included in the study. The total number of study participants was 8,780. The pooled prevalence of discontinuation of long acting reversible contraceptive use was 36.94% (95% CI: 28.547–45.326). According to sub-group analysis, Amhara region (45%) and institution-based studies (47.9%) had the highest prevalence. The most common reason for contraceptive discontinuation was negative side effect (42.3%). Women experienced side effects (AOR = 2.833:95% CI:2.005–4.003), didn't receive counseling on side effects (AOR = 2.417; 95% CI: 1.591–3.672), didn't appoint follow up (AOR = 2.820; 95% CI: 2.048–3.881), dissatisfied with the given service (AOR = 5.156; 95% CI: 3.644–7.296), and a desire to be pregnant (AOR = 2.366; 95% CI: 1.760–3.182) were predictors of discontinuation of contraceptives. Conclusion In Ethiopia, the pooled prevalence of long acting contraceptive discontinuation was high. Side effects, not being informed about side effects, dissatisfaction with the provided service, no insertion follow-up, and a desire to become pregnant were all associated factors. Healthcare professionals should focus on the client's reproductive goals, proper management of side effects, counseling, and post-insertion visits. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022347860, identifier CRD42022347860.